Pengaruh E-SPT, Sanksi, Sosialisasi, Pengetahuan Perpajakan, dan Moralitas pada Kepatuhan Wajib Pajak - Lhoka, Ni Luh Putu Dian Patni; Sukartha, I Made (E-Jurnal Akuntansi; Vol 30 No 7 (2020)DO - 10.24843/EJA.2020.v30.i07.p07, 2020)
Taxes are the largest source of state revenue in Indonesia. Compliance is an important factor in increasing tax revenue because tax compliance is the attitude of compliance, compliance, submission, and application of tax provisions. This research was conducted at KPP Pratama Tabanan using a sample of 390 non-employee taxpayers who were determined using the nonprobability sampling method with accidental sampling technique. The data analysis method used in this study is multiple linear regression analysis. The results found that, e-SPT, sanctions, socialization, tax knowledge, and morality had a positive effect on the tax compliance of non-employee individuals registered at the KPP Pratama Tabanan. Keywords: E-SPT; Sanctions; Socialization; Taxation Knowledge; Morality; Taxpayer Compliance.